Efforts to Overcome Difficulties in Reading Hijaiyah Letters Through the Index Card Match Learning Model on Elementary School Students - Syahrani, Amelia; Akbar, Muhammad; Ramadhan, Muh. (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to overcome students’ difficulties in reading Hijaiyah letters through the implementation of the Index Card Match learning model among second-grade students of SD Negeri 4 Lamokato. This research employed a qualitative approach using Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 20 second-grade students. Data collection techniques included Hijaiyah letter reading tests, observation of students’ learning activities, interviews, and documentation. Data analysis was carried out quantitatively by calculating learning mastery percentages and qualitatively through data reduction, data display, and conclusion drawing. The results indicate that the implementation of the Index Card Match learning model effectively improved students’ Hijaiyah letter reading skills and learning activities. The learning mastery percentage increased from 25% in the pre-cycle to 55% in Cycle I and significantly improved to 90% in Cycle II. Students’ learning activities also increased, with an average of 90% in Cycle II. Therefore, it can be concluded that the Index Card Match learning model is effective in overcoming difficulties in reading Hijaiyah letters among second-grade students at SD Negeri 4 Lamokato.